2023
DOI: 10.1111/all.15822
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E autoantibodies in atopic dermatitis associate with Type‐2 comorbidities and the atopic march

Inge Kortekaas Krohn,
Fariza Mishaal Saiema Badloe,
Nadine Herrmann
et al.

Abstract: BackgroundAutoreactive immunoglobulin E (IgE) antibodies to self‐peptides within the epidermis have been identified in patients with atopic dermatitis (AD). Prevalence, concomitant diseases, patient characteristics, and risk factors of IgE autoantibody development remain elusive. We aimed to determine IgE autoantibodies in serum samples (n = 672) from well‐characterized patients with AD and controls (1.2–88.9 years).MethodsAtopic dermatitis patients were sub‐grouped in AD with comorbid Type‐2 diseases (“AD + T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…A recent study suggests that immunoglobulin E (IgE) autoantibodies could be biomarkers for AM. 65 This cross-sectional study found that AD patients with other type 2 comorbidities had higher levels of autoreactive IgE compared to those with only AD. Notably, a significant majority of AD patients with elevated autoreactive IgE also had type 2 comorbidities.…”
Section: Current Candidate Biomarkers Of Admentioning
confidence: 71%
See 2 more Smart Citations
“…A recent study suggests that immunoglobulin E (IgE) autoantibodies could be biomarkers for AM. 65 This cross-sectional study found that AD patients with other type 2 comorbidities had higher levels of autoreactive IgE compared to those with only AD. Notably, a significant majority of AD patients with elevated autoreactive IgE also had type 2 comorbidities.…”
Section: Current Candidate Biomarkers Of Admentioning
confidence: 71%
“… 48 Also, sensitization to self-proteins has been thought to cause AD, which is distinct from the classic AD clinical phenotype. 65 Nonetheless, the utility of these biomarkers is viewed differently in clinical trials and clinical settings, since the clinical efficacy of particular therapies for AD is best measured by clinicians and patients through visual assessments.…”
Section: Current Candidate Biomarkers Of Admentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of studies with a sample size greater than 100 showed a range of 23%–28% in eczema patients 98 . A recent study including 672 subjects found a prevalence of 16.4% in patients with AD and atopic comorbidities, 9.6% in patients with solely AD, 9.6% in atopic controls without AD, and 2.7% in non‐atopic subjects 99 …”
Section: Autoreactive Ige In Atopic Dermatitismentioning
confidence: 99%
“…98 A recent study including 672 subjects found a prevalence of 16.4% in patients with AD and atopic comorbidities, 9.6% in patients with solely AD, 9.6% in atopic controls without AD, and 2.7% in nonatopic subjects. 99 The levels of IgE AAb in AD patients are correlated with disease severity. 84,89,91,93,[100][101][102] Therefore, it is held that their presence is clinically relevant, but their precise pathophysiological contribution still requires further investigations.…”
Section: Autore Ac Tive I G E In Atopi C Dermatitismentioning
confidence: 99%